EXTREME Sr–Nd–Pb–Hf ISOTOPIC COMPOSITIONS EXHIBITED BY THE TINAQUILLO PERIDOTITE MASSIF, NORTHERN VENEZUELA: IMPLICATIONS FOR GEODYNAMIC SETTING - Choi S.H.; Mukasa S.B.; Andronikov A.V.; Marcano M.C. (My University, 2007)
An origin of the Tinaquillo Peridotite Complex in northern Venezuela, and a model for the tectonic framework of the boundary zone between the southern Caribbean Plate margin and the South American Plate (SAP) during Late Jurassic to Mid-Cretaceous time are developed using newly measured Sr, Nd, Pb and Hf isotopic compositions as well as major and trace element geochemistry for some hornblendite veins and their spinel peridotite host rocks. Depleted geochemical characteristics, principally major element concentrations, and Nd and Hf isotopes (e.g., εNd = + 27; εHf = +50; ca. 3.4 Ga-Nd model age) of the Tinaquillo peridotites suggest a genetic link between this complex and the Guiana Shield farther to the south within Venezuela. Scattered zones within the Tinaquillo peridotite were overprinted by what we interpret as channelized hydrous fluids (<~3%) derived from the eastward-dipping subduction of the Farallon Plate beneath the SAP in the Late Jurassic, leading to modification of the original Sr, Nd and Hf isotopic compositions as well as the incompatible element concentrations. The hornblendite veins have Sr, Nd, Pb and Hf isotopic compositions, falling within the range of present-day Pacific/Atlantic MORB, but trace element abundance patterns with combinations of arc- and MORB-like characteristics. These results rule out the possibility of local melting of the host peridotites to produce magmas from which the hornblendite veins formed. We suggest that during inception of the westward-dipping subduction of the Protocaribbean Plate immediately following polarity reversal in the Mid-Cretaceous, melts infiltrated the mantle lithosphere and produced the veins.
Keywords: LITHOSPHERIC MANTLE; LIGHT RARE EARTH ELEMENT; DEPLETE MANTLE; SPINEL PERIDOTITE; HYDROUS FLUID; Cretaceous; Jurassic; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская